G82(P) Hepato-cerebral mitochondrial DNA depletion: a rare and fatal cause of prolonged neonatal jaundice. (7th April 2014) - Slattery, S; Broderick, AM; Fraser, B; Hughes, J; Knerr, I; Crushell, E
Abstract : Case presentation: The only child of consanguineous moroccan parents presented at 6 weeks of age with poor weight gain and prolonged jaundice. He was profoundly hypotonic and not yet smiling or fixing and following. Investigations revealed severe hepatic dysfunction, elevated lactates, hypoglycaemia and abnormal urine organic acids (consistent with mitochondrial dysfunction). Cranial ultrasound scan, ophthalmology and cardiology assessments were normal. Muscle biopsy was histologically normal and muscle mitochondrial respiratory chain complexes were normal. Liver biopsy showed cholestasis, lobular disarray and large droplet steatosis and decreased resp chain complexes I, II&III (combined) and IV activities. This pattern is suggestive of mitochondrial DNA (mtDNA) depletion. Hepatic mtDNA content was confirmed to be just 6% of expected normal mtDNA content. Genetic analysis showed homozygosity for a deletion in exon 4 of the MPV17 gene, a gene necessary in mtDNA replication. This gene is one of a number of genes, all involved in mtDNA replication or maintenance, that are associated with hepatocerebral mtDNA depletion syndromes, clinically sometimes known as Alpers syndrome. Despite normal muscle respiratory chain levels, mtDNA depletion was also present in muscle with just 25% of normal mtDNA content present. Unfortunately his clinical course continued to progress and he died at 7 months of age. Conclusion: Hepato-cerebral depletion syndromes are heterogenous and may present at any age. They are rare but should be suspected with a clinical combination of neurological, hepatic and metabolic abnormalities. Timely diagnosis is very important as this diagnosis is an important factor in decision making around liver transplantation.